Low‐Dimensional Saturable Absorbers in the Visible Spectral Region. Issue 1 (30th August 2018) - Zhang, Yuxia; Lu, Dazhi; Yu, Haohai; Zhang, Huaijin
Abstract: Visible light has an important and unique value in research and practical applications, because of its perceptible characteristics by the human eye. Directly pumped bulk visible pulsed lasers are booming in recent years stimulated by the advances of blue laser diodes. As critical components, novel and favorable saturable absorbers in view of distinct nonlinear saturable absorption properties are desired, which can promote the development of ultrafast photonics in the visible range. Over the years, low dimensional materials with the advantages of ultrafast carrier recovery rate and distinct nonlinear saturable absorption have originated a class of innovative applications in photonics and optoelectronics, especially as saturable absorbers in the pulsed lasers. Here, the low dimensional saturable absorbers in the visible range are reviewed, including the fabrication, linear and nonlinear optical response, and applications in the pulsed visible lasers of low dimensional semiconductors and noble metal nanoparticles. The design criteria of the low dimensional saturable absorbers for generating laser pluse by Q ‐switching and mode‐locking are proposed and discussed. Finally, some possible development tendency and directions of saturable absorbers for the visible pulsed lasers are proposed in this review by focusing on some potential strengths. Abstract : Saturable absorbers with appropriate nonlinear properties in the visible range are desired and boosted with the development of laser diode pumped lasers. Low dimensional materials are reviewed from optical properties to applications in the visible range. The design criteria for saturable absorbers are built and verified by reviewing low dimensional materials. The possible prospects are proposed for ultrafast photonics.